Laterality of head position at rest in mallard (Anas platyrhynchos) from two distinct northern wintering groups - Birina, Uliana; Malashichev, Yegor (Biological Communications, 2015)
Motor asymmetries are wide spread among vertebrate and invertebrate animals. More frequently asymmetries in the use of paired appendages and turns of the body in space become the subject of research. Unpaired organs, positioned along the long axis of the body become the subjects of investigation of the functional asymmetries less often. Here we performed a preliminary estimation of populational characteristics of asymmetry in the turn of the head while resting in Mallards (Anas platyrynchos) from two distinct wintering groups. On tracks along the banks of rivers and channels in the center of Saint-Petersburg, Russia, and along the Buksnesfjord at the Vestvagøy island (Lofoten Islands, Norway Sea, Norway), we recorded the position of the head (under the left wing, or under the right wing) in resting birds ones for each individual. Totally we recorded head position in 151 individuals from Saint-Petersburg and in 77 individuals at Vestvagøy. Individuals keeping heads under the right wing were predominant in Saint-Petersburg, while at Vestvagøy the proportion of «left» and «right» individuals did not differ significantly from 1:1. Difference between the populations was significant, while sex differences in both populations were not found. We discuss possible reasons for the differences in population characteristics of asymmetry in the head position («head-under-wing»), particularly conditions of wintering, birds behaviour. We conclude that the study of different wintering groups of mallards can be possibly perspective for estimation of population status by assessment of relative proportion of «left» and «right» birds.